Guardian of the Snacks: Toward designing a companion for mindful snacking. Issue 2 (June 2021) - Khot, Rohit Ashok; Aggarwal, Deepti; Yi, Jung-Ying (Lois); Prohasky, Daniel
COVID-19 has brought significant changes to our lives and eating practices, where many of us are required to not only stay at home but also eat at home. This is particularly challenging for lone-person households as eating alone can be boring, less motivating and could lead to unhealthy behaviors such as mindless snacking or skipping of meals. To remedy such situations, we present Guardian of the Snacks, a tangible multimodal system that encourages mindful snacking by offering a playful companionship to snacking. The system is customizable to bear the shape of different animals and can be adapted to different snacking scenarios. Like a good companion, it encourages eating but moderates overeating through auditory feedback and playful nudging. In this article, we reflect on our design process and contribute ideas for the future development of technology-driven mindful snacking.